Multifunctional agriculture, non-trade concerns and the WTO - Lankoski, Jussi (Maatalouden taloudellinen tutkimuslaitos, 2000)
While the term multifunctionality is new in the international trade debate, the concept of multifunctional agriculture is not novel in the domestic agricultural policy context, since for decades countries have pursued several non-food or non-economic goals through domestic agricultural policies. However, due to the nature of the joint production process, involving both complementarities and trade-offs, sustaining and enhancing the multifunctional character of agriculture provides a challenging task for domestic policy design. The green box of the Uruguay Round Agreement on Agriculture (AoA) seems to provide effective measures for addressing the non-trade concerns and multifunctional objectives through targeted policies. The flexibility of the domestic policy design is, however, influenced by the amber box commitments under the terms of the AoA. Countries whose amber box commitments are binding may have to rely solely on the green box measures for sustaining and enhancing multifunctional agriculture.
Keywords: Ma; WTO; vihreä laatikko; monivaikutteisuus; ei-kaupalliset kysymykset; green box; multifunctionality; non-trade concerns; WTO